2015
DOI: 10.1093/schbul/sbv074
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of DNA Methylation Between Blood and Brain Tissue and Its Application to Schizophrenia Research

Abstract: Given the difficulty of procuring human brain tissue, a key question in molecular psychiatry concerns the extent to which epigenetic signatures measured in more accessible tissues such as blood can serve as a surrogate marker for the brain. Here, we aimed (1) to investigate the blood-brain correspondence of DNA methylation using a within-subject design and (2) to identify changes in DNA methylation of brain-related biological pathways in schizophrenia.We obtained paired blood and temporal lobe biopsy samples s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
178
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 246 publications
(193 citation statements)
references
References 53 publications
11
178
0
4
Order By: Relevance
“…Nevertheless, findings from our previous studies focusing on peripheral OT levels and social cognition, which have used the present assay methodologies (7), have been replicated by researchers using different assay methods (9). Fifth, we focused on methylation levels of a single CpG site in the promoter region of OXTR and assayed peripherally derived DNA from blood which are imperfect markers of brain DNA methylation (86). Although we do not know the exact association between blood and brain methylation at CpG site -934, a number of studies to date reflect the utility of this peripheral assay in predicting brain endophenotypes related to social cognition (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, findings from our previous studies focusing on peripheral OT levels and social cognition, which have used the present assay methodologies (7), have been replicated by researchers using different assay methods (9). Fifth, we focused on methylation levels of a single CpG site in the promoter region of OXTR and assayed peripherally derived DNA from blood which are imperfect markers of brain DNA methylation (86). Although we do not know the exact association between blood and brain methylation at CpG site -934, a number of studies to date reflect the utility of this peripheral assay in predicting brain endophenotypes related to social cognition (34, 35).…”
Section: Discussionmentioning
confidence: 99%
“…However, the studies on this topic are still controversial, and some findings indicate that most DNA methylation markers in peripheral blood do not reliably predict brain DNA methylation status (Walton et al, 2016). Only a specific subset of peripheral data was shown to proxy methylation status of brain tissue, which suggests that studies on peripheral methylation should ideally restrict their analysis to these markers (Walton et al, 2016).…”
Section: Perspectivesmentioning
confidence: 99%
“…Third, although the use of peripheral tissue samples hold potential for the identification of exposure/risk biomarkers, the extent to which findings may reflect methylation changes in the brain is unclear. In fact, a recent study [26] found that most DNA methylation markers in peripheral blood do not reliably predict brain DNA methylation status, making inferences on brain-relevant processes difficult. As such, it will be important to establish to what extent peripheral levels of IGF2 methylation relate to in vivo structural/functional neural markers of ADHD.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%